DIVERSITY OF MACROMYCETES OF RAVINE BIRCH FORESTS ON THE LEFT BANK OF THE URAL RIVER WITHIN THE WEST KAZAKHSTAN REGION (Experimental biology, 2024)
Biodiversity and its conservation remain fundamental aspects of contemporary biology, continually sparking interest and requiring active research. Presently, significant disparities persist in our understanding of the distribution and habitats of various living organisms. Among the most diverse and crucial groups warranting intensive and comprehensive analysis are fungi. The data obtained significantly contributes to the study of macromycete diversity within the birch forests of the Ural River valley. However, information regarding these fungi within the territory of Kazakhstan remains incomplete and fragmented.The article presents data on the biodiversity of the mycobiota within the ravine birch forests situated along the left bank of the Ural River in the West Kazakhstan region. As of the current date, the biota study has identified 43 species belonging to 26 genera, spanning across 17 families and six orders. Predominant families include Polyporaceae, Russulaceae, Pluteaceae, Amanitaceae, and Strophariaceae. The trophic analysis of the mycobiota within birch forests revealed a notable diversity of xylotrophs, with 25 species identified, primarily associated with the families Fomitopsidaceae, Polyporaceae, Pluteaceae, and Strophariaceae. Additionally, the group of mycorrhizal fungi comprises 15 species, predominantly represented by the families Amanitaceae, Boletaceae, Russulaceae, and Paxillaceae.Thus, the highest richness of macromycetes is noted in birch forests located in the lowlands of deep gullies. Species diversity of macromycetes tends to decrease in birch forests growing along slopes of various orientations, along the edges of gullies, and on eroded slopes. Moreover, in new pioneer sites such as the sole of the indigenous bank of the Ural River, the species composition of mushrooms is notably impoverished. This study represents the first taxonomic analysis of mycobiota diversity in the ravine birch forests.
Keywords: macromycetes; birch forests; Ural river valley; West Kazakhstan Region; species composition; biodiversity